Hallux Valgus Angular Measurements using WBCT Semiautomatic and Manual Assessments. Issue 4 (November 2022) - Carvalho, Kepler; Walt, Jennifer S.; Ehret, Amanda; Tazegul, Tutku; Mallavarapu, Vinnel; Rojas, Edward O.; Dibbern, Kevin N.; Mansur, Nacime SB; Lalevée, Matthieu; Netto, Cesar de Cesar
Category: Bunion; Lesser Toes; Midfoot/Forefoot Introduction/Purpose: Radiographic measurements are an essential tool to determine the appropriate surgical treatment and outcome for Hallux Valgus (HV). WBCT already demonstrates significant advances that include the ability to perform traditional measurements for HV in the 3D setting reliably, as well as a more complete and accurate evaluation of the deformity. In addition, new software with an advanced semi-automated segmentation system obtains semi-automatic 3D measurements of WBCT scan data sets, minimizing the errors in reading angular measurements. The objective was (1) to assess the reliability of WBCT computer-assisted semi-automatic imaging measurements in HV, (2) to compare semi-automatic with manual measurements in the setting of an HV, and (3) to compare semi-automatic measurements between HV and control group. Methods: In this retrospective IRB (ID# 201904825) approved study, we assessed patients with hallux valgus deformity. The sample size calculation was based on the hallux valgus angle (HVA). Thus, to obtain the 0.8 power, including 26 feet with HV in this study, was necessary. Our control group consisted of 19 feet from 19 patients without HV. Raw multiplanar data was evaluated using software CubeVue. In the axial plane, hallux valgus angle (HVA), intermetatarsal angle (IMA), and interphalangeal angle (IPA) were measured. The semiautomatic 3D measurements were performed using the Bonelogic Software. Inter-rater reliabilities were performed using ICC. Agreement between methods was tested using the Bland-Altman plots. The difference between Pathologic and Control cases using semi-automatic measurements was assessed with the Wilcoxon signed-rank test. Alpha risk was set to 5% (α = 0.05). P<= 0.05 was considered significant. Results: Intraobserver and Interobserver agreement and consistency for Manual and Semi-automatic WBCT measurements assessed by ICC demonstrated excellent reliability in both cases. However, when comparing Manual and Semi-automatic measurements for HVA, IMA, and IPA, Semi-automatic measurements showed the highest values. Agreement between manual (M) and semi-automatic (SA) methods was tested for HVA, IMA and IPA using the Bland-Altman plots. The results indicated a high correlation between the parameters calculated from the manual and semi-automatic measurements, and a strong agreement between the readers and the software. Comparison between pathological group with HV and control (standard) group without HV using semi-automatic measurements was capable of differentiating pathological (HV) from non-pathological conditions for the HVA and IMA angles (p < 0, 05). Conclusion: Semi-automatic measurements are reproducible and comparable to measurements performed manually. The software differentiated pathological from non-pathological conditions when subjected to semi-automatic measurements. The development of advanced semi-automatic segmentation software with minimal user intervention is essential for the establishment of big data and can be integrated into clinical practice, facilitating decision-making.